Global Smooth Solutions and the Asymptotic Behavior of the Motion of a Viscous, Heat-conductive, One-dimensional Real Gas (Journal of Partial Differential Equations, 1998)
The system of balance laws of mass, momentum and energy for a viscous, heal-conductive, one-dimensional real gas is considered. The existence of globally defined smooth solution to an initial boundary value problem is established. Because of the boundary conditions' effect, vacuum will be developped as time tends to infinity.
Keywords: Global (local) existence; a priori estimate; the asymptotic behavior